Antioxidant and Biocompatible 5‐O‐Caffeoylquinic Acid‐Based Composite Materials. Issue 1 (20th February 2020) - Pacifico, Severina; Piccolella, Simona; Naviglio, Silvio; Catauro, Michelina
Abstract: Silica/5‐ O ‐caffeoylquinic acid hybrid materials are synthetized via sol–gel route, obtaining new biomaterials able to preserve the antioxidant capability of the natural nutraceutical phenol compound. The materials are chemically characterized through FT‐IR and UV spectroscopy, whereas their bioactivity is ascertained by both scanning electron microscopy and FT‐IR analysis. The antioxidant efficacy is assessed, applying DPPH and ABTS methods, and direct MTT test on NIH‐3T3 cells is employed to preliminarily evaluate the biocompatibility. This latter seems to strongly depend on the amount of entrapped phenol.